DEVELOPMENT OF A CONTROL ALGORITHM FOR A SMART IRRIGATION SYSTEM BASED ON SOIL MOISTURE AND METEOROLOGICAL DATA - Rokhmonov, Durbek; Sulaymonov, Jasurbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article proposes an intelligent control algorithm based on soil moisture and weather (meteorological) data to develop an effective irrigation regime for agricultural lands. The system collects and analyzes data in real time through IoT devices, and irrigation is carried out automatically or semi-automatically. The proposed approach serves to increase water use efficiency, reduce energy consumption, and improve crop yield.